The nurse’s performance in prenatal care offered in Primary Health Care (Research, Society and Development, 2023)
The objective was to understand the role of nurses in prenatal care offered in Primary Health Care. This is a qualitative, descriptive-exploratory research, developed with eleven nurses working in Family Health Strategies in a municipality in the extreme west of Santa Catarina. Data collection took place through semi-structured interviews, which were recorded and later transcribed in full. For data analysis, Content Analysis, proposed by Minayo, was used. After the analysis, two thematic categories emerged: perceptions and actions of nurses in prenatal care; and, difficulties encountered by nurses in carrying out prenatal care in Primary Health Care. From the study, it is clear that many of the nurses interviewed do not perform the Nursing Consultation, although they recognize its importance in prenatal care. However, it is evident that the reception, dialogue, guidance and bond building with the pregnant women are carried out, activities that are only possible through consultation. Given this, it is important for these professionals to establish the Systematization of Nursing Care, through the operationalization of the Nursing Process, so that the Nursing Consultation is systematized, resolutive and, in fact, recognized by nurses, the health team and by pregnant women.